БАНК ӨТІМДІЛІГІ: БАСҚАРУ, БАҒАЛАУ ЖӘНЕ ТАЛДАУ - Шаяхметова, К О; Керімбекова, Н Н (Journal of Economic Research & Business Administration, 2015)
In this article main objectives of management by liquidity of bank, calculation liquidities in Republics Kazakhstans, main objectives, stages and conditions of the analysis of liquidity of bank are considered. High liquidity of bank are a source of the constant income.